Pengaruh Pendapatan Daerah terhadap Belanja Daerah Provinsi Jawa Tengah - Purwantoro Purwantoro; Lilis Setyowati (Jurnal Bisnis dan Ekonomi, 2019)
Regional autonomy policy has brought about major changes in the patterns of local governance. Regional government are required to maximize the potential in administering government, because regional autonomy make regional government have a more dominant role than before. In addition, local governments are required to have an actual development program such as prioritize allocation of capital expenditure. This study aimed to analyze local generated revenue(PAD), which is the original source of local government revenue and balance funds are transfers from central government to local shopping districts / cities in Central Java province. Based on F test, it can be concluded that the variable regional revenue and equalization funds simultaneously significant effect on their spending. The results of the t test showed that the variables of regional revenue and equalization fund significant positive effect on regional spending